2019
DOI: 10.1155/2019/3758527
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental Study on the Effects of Initial Shear Stress and Vibration Frequency on Dynamic Strength of Saturated Sands

Abstract: The cyclic triaxial system is used to investigate the effects of confining pressure, initial shear stress, cyclic stress ratio, and vibration frequency on the dynamic strength characteristics of saturated sand in the Wenchuan area. Results show that when the vibration frequency is constant, the dynamic strength of sand increases with the increase of the consolidation ratio. However, when the consolidation ratio exceeds a certain value, the dynamic strength of sand decreases or increases slowly. The dynamic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Taking into consideration of the aforementioned condition, 1 Hz and 0.1 Hz frequency are generally preferred for coarse-grained soil (sandy type) and fine-grained soil (silty type), respectively [62,63]. Based on the analysis of seismic events, Zhang et al [64] also adopted frequency starting from 1 to 3 Hz for saturated sand. However, many studies on dynamic properties of soil considered frequency range in between 0.5 and 2 Hz [65][66][67].…”
Section: Parameters Considered For the Present Studymentioning
confidence: 99%
“…Taking into consideration of the aforementioned condition, 1 Hz and 0.1 Hz frequency are generally preferred for coarse-grained soil (sandy type) and fine-grained soil (silty type), respectively [62,63]. Based on the analysis of seismic events, Zhang et al [64] also adopted frequency starting from 1 to 3 Hz for saturated sand. However, many studies on dynamic properties of soil considered frequency range in between 0.5 and 2 Hz [65][66][67].…”
Section: Parameters Considered For the Present Studymentioning
confidence: 99%
“…Much research has been conducted on the behavior of sand under cyclic loading using cyclic triaxial tests, with the focus being on the effects of confining pressure, loading amplitude and frequency, over-consolidation ratio, fine particle content, and relative density, etc. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Sharma and Maheshwari [21] conducted cyclic triaxial tests on sands with different degrees of saturation and found that the damping ratio of saturated sand is greater than that of dry sand and partially saturated sand.…”
Section: Introductionmentioning
confidence: 99%
“…Bu zemin elemanları herhangi bir ilave gerilme öncesinde de kayma gerilmelerine maruz durumdadırlar. Özellikle drenajsız şartlar altında, kumlu zeminlerin tekrarlı yükler altındaki davranışları üzerinde başlangıç statik kayma gerilmesinin etkileri sıvılaşma direnci açısından oldukça önemli bir konu olup günümüzde halen birçok araştırmacı tarafından ele alınmaktadır [2,[4][5][6]. Bu çalışmalar, başlangıç statik kayma gerilmesi varlığının, doygun kumların dinamik özelliklerini etkileyen önemli bir faktör olduğunu ortaya koymakta ve bu etkiyi yansıtabilmek için düzeltme faktörleri (Kα) önermektedirler.…”
unclassified